2019
DOI: 10.1177/0960327119873017
|View full text |Cite
|
Sign up to set email alerts
|

Transgenerational effect of parental obesity and chronic parental bisphenol A exposure on hormonal profile and reproductive organs of preadolescent Wistar rats of F1 generation: A one-generation study

Abstract: There is a global concern about adverse health effects of endocrine-disrupting chemicals (EDCs). Bisphenol A (BPA), an estrogenic and obesogenic compound, used in the plastic and medical industry has a dominant position among EDCs as far as human health and regulatory scenario are concerned. Due to its omnipresence across the biosphere, population of all age groups and health status is unavoidably exposed to BPA. Transgenerational exposure to BPA and its effects have also been recognized. However, there is no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Tail impairment, sperm hook curvature, poor sperm morphology, follicle cell loss in the primordial, and cell loss in the stroma are just a few examples of data supporting this claim. This type of anomaly can be handed on through the F1 lineages [ 16 ]. This is because BPA has the ability to induce obesity to be passed down through the generations through epigenetic transgenerational inheritance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tail impairment, sperm hook curvature, poor sperm morphology, follicle cell loss in the primordial, and cell loss in the stroma are just a few examples of data supporting this claim. This type of anomaly can be handed on through the F1 lineages [ 16 ]. This is because BPA has the ability to induce obesity to be passed down through the generations through epigenetic transgenerational inheritance.…”
Section: Resultsmentioning
confidence: 99%
“…Since glucose metabolism plays a vital role in spermatogenesis, impaired glucose tolerance greatly affects the normal function and structure of the sperm. In female subjects, stromal cell loss due to the increased level of oxidative stress, and the decreased level of SOD, GSH, or GPx may further enhance the transmission of the defects through reproductive organs [16]. Another study shows that BPA exposure in prenatal interferes with miRNA expression, causing 15 related genes to insulin signaling to be affected.…”
Section: Bpa and Transgenerational Effects Of Obesitymentioning
confidence: 99%
“…It reveals that there is a probability of loss in relatedness between body weight and testicular weight, nonetheless, its chances are highly unlikely at this particular dose. Various earlier studies have noted increase in body weight while reduction in testicular weight following low dose exposure of BPA [34,35,36,37]. Thus, it is possible to assume an inverse proportionality between body and testicular weight.…”
Section: Discussionmentioning
confidence: 97%
“…They concluded that, with their experimental range of BPA, the higher the dose to which the animals are exposed perinatally, the earlier its effect on glucose metabolism in the offspring. Dabeeret et al [68] studied the effects of exposure to low doses of BPA (10 ppmx180 days) in the F0 generation of obese Wistar rats and its impact on the F1 generation, analyzing it on day 35 post-birth. It was observed that there were no differences in the serum glucose patterns of the F1 exposed in relation to the control, which would reveal the compensatory capacity of the organism, in which the glucose levels returned to the normal ranges of the species, although it would be interesting to elucidate if the tissue damage would be fully recovered.…”
Section: Biochemical Parametersmentioning
confidence: 99%